Vocabulary introduction about word classes for Al-Islah Islamic Kindergarten teachers, Sukoharjo - Nunun Tri Widarwati; Purwani Indri Astuti; Ratih Wijayava (Universitas Muhammadiyah Magelang, 2023)
The community service program was carried out with encouragement to improve the ability and understanding of word classes in English for kindergarten teachers, especially TKIT Al-Islah, Jombor Village, Mojolaban District, Sukoharjo. The material presented consists of pronoun, verb, adjective, noun, and adverb. Service activities in the form of this training begin with pretest questions and end with post tests. The evaluation showed an increase in word classes knowledge in English where the pretest results were 72 to 90 during the posttest. Thus, it is expected that teachers can develop English learning materials by utilizing their word classes knowledge.